Flume Experiments on Wood Debris Jam at An Arch Bridge in Upstream River Reach during Flash Flood - Muhammad Islamy Rusyda; Shinya Ikematsu; Haruyuki Hashimoto (Jurnal Teknik Sipil dan Perencanaan)
Abstract During our field surveys, two types of woody debris deposition were found. One is deposition of individual wood pieces and the other is formation of woody debris jams at obstructions such as a bridge. To investigate behavior of wood debris jam at a bridge, a series of flume experiments was performed in a smooth acrylic rectangular flume. A model of an arch bridge was used as an obstacle in river. The arch bridge was based on Yoriguci bridge. Wooden cylinder was used as model of wood debris. An interpretation of experimental results shows that the wood debris jam can be determined by number of released wood pieces and shaded area of obstructions. These experimental results also reveal that wood debris jam formed by the model bridge contribute to backwater rise. From investigation on flow around model bridge, it is clearly shown the presence of backwater rise caused by the number of wood pieces trapped by a model of an arch bridge. The results also show that the loss coefficient depends on trapped wood pieces. A simple procedure was proposed in this study which seem to provide for predicting backwater rise due to wood debris jam at obstructions.